Residual da mistura formulada dos herbicidas imazethapyr e imazapic em áreas de arroz sob diferentes manejos de solo - Kraemer, Alejandro Fausto (2008)
Red rice (Oryza spp.) is one of the main limiting factors of rice yield (O. sativa L.) in the world and particularly in the Rio Grande do Sul (RS) state Brazil. The Clearfield® technology is a viable and efficient tool for controlling such harmful plant by using imidazolinone herbicides in tolerant cultivars. However, herbicides may persist on the soil after the crop season in amount that could affect the future use of the area with other crops as well as with non tolerant rice cultivars. The persistence of this kind of herbicides is highly dependent on the soil s environmental conditions. It increases in low pH soils with high organic matter (MO) content, and under anaerobic conditions. The main way of herbicide dissipation is the biodegradations; they can be photolysis or be lixiviated bellow the roots absorption region. Two field experiments were carried out on lowland soil in Santa Maria-RS during 2006/2007. The first experiment (Chapter II) had the objective of determining the effect of nine soil tillages (four on no till or minimum till seeping and five, on conventional tillage) on the phytotoxicity of non tolerant rice. The residual effect of the herbicide Only® affected plants stand, tillering, panicle number and plant heights of cultivar IRGA 417, but did not affect the grain yield. Soil plowing decreased herbicide activity on the soil surface (0-3 cm) without affecting the variables assayed. The second experiment (Chapter III) had the objective of determining the effect of two soil tillages (no till- PD- and conventional tillage-PC) on imazethapyr degradation and leaching. Higher degradation of imazethapyr was registered on PC than on PD. Imazethapyr leaching until 20 cm regardless the tillage system. In PC, a uniform distribution of imazethapyr was observed in the first 15 cm of soil while in PD there was a lower concentration of imazethapyr at 0-5 cm, which accumulated at 5-15 cm deep.